Restorative justice programs and practices in juvenile justice: an updated systematic review and meta-analysis for effectiveness - Kimbrell, Catherine S. (Criminology & public policy, 2023)
Research summary Restorative justice (RJ) in practice has taken on many different forms. It is argued that RJ does not have definitional boundaries, making it hard to limit its essence to that of a particular program, practice, philosophy, or outcome. Therefore, this study's objective was to systematically review and statistically synthesize all available research on RJ programs and related programs and practices using meta-analytic methods. Our updated systematic search and meta-analysis identified a total of 57 unique studies including 79 evaluations (including 18 random assignment and 61 quasi-experimental designs). We extracted a total of 631 effect sizes related to delinquency, non-delinquency, and victim outcomes. The results of our meta-analysis showed that RJ programs and practices are associated with a small-to-moderate and statistically significant reduction in future delinquent behavior relative to more traditional juvenile justice responses (g = 0.23, 95% CI [0.14, 0.32]). Nevertheless, results were smaller for the more rigorous random assignment studies and nonsignificant, raising concerns about the robustness of this finding. Our most promising findings, however, were for the victim and non-delinquency outcomes. Policy implications The bottom line for RJ programs and practices is that the empirical evidence is supportive of these programs in moderately reducing juvenile delinquency. However, the evidence appears more promising in the area of non-delinquency outcomes for victims and youth participants involved in these programs. Taken together, the results indicate that RJ programs and practices may be effective at reducing recidivism, albeit to a small-to-moderate extent, but have the added feature of meaningfully increasing perceptions of satisfaction and fairness for victim and youth participants. These results should be viewed as encouraging for policy makers, RJ practitioners, and proponents that emphasize the centrality of the victim in the process of crime and harm resolution, as well as those interested in alternative solutions to addressing youth crime.